The role of leader-member exchange in the organizational citizenship behavior according to organizational trust Analytical research at the center of Ministry of Migration and Displaced - سعيد, هديل كاظم; عبد الستار, حلا صاحب (Journal of Economics and Administrative Sciences, 2014)
This research aimed to examine the correlation and influence of leader-member exchange in the organizational citizenship behavior in the existence of organizational trust as mediator variable among workers in ministry of migration and displaced, has been collecting data and information relating to research by designing questionnaire was distributed to the stratified random sample included (56) member of the workers in the ministry mentioned, and through the use of several statistical method were the main findings of research was the existence of a correlation relationship and influence between leader- member exchange and organizational trust, while the results confirmed no correlation and influence exist between leader- member exchange and organizational citizenship behavior. The research ended with a group of Conclusions The most prominent of the organizational trust important role in increasing the impact of leader- member exchange of the Organizational Citizenship Behavior, And it recommended that research on the need for the Planning Directorate in the Ministry of Displacement and Migration work poll periodically to the views of staff for the running of the ministry and the relationship between supervisor and there Subordinates, it would provide for the heads of sources to develop their performance as well as enhance their openness and transparency, which requires that takes presidents including posed by subordinates of Notesand ideas.